To the inclusive education: a systematic - Martínez, Mayluc (2019)
In the framework of the current dissertation, from a systemic approach, the process of inclusive education, seen as a complex phenomenon in which interact, in addition to the subject itself, which are the learners, various actors, systems and subsystems: the Family, the school as an institution, the teachers, the curriculum, the support professionals, the institutions that provide psychoeducational and therapeutic services, among others. It is opportune to highlight that this working paper is a product of both a theoretical review as a reflection that arises from the practice that takes place in the context of our institution (Organization Psychoeducational TAEHO. In this ideas order, we try to learn not only how such elementswork (doing particular emphasis on the family, on the school and on the professional of support), but the interconnections that are established between them in the context of this totality, departing from necessary diagnoses and realizing pertinent analyses, in relation both with the diversity of the subjects (students, participants) and with the heterogeneity of the educational institution and its context. In this way, it is expected to reach an understanding of the educationalprocess in its entirety, as the only way to ensure that it is synergistic, harmonious and, above all, inclusive.